The DNA Polymerase _-Primase Complex: Multiple Functions and Interactions - Marco Muzi-Falconi; Michele Giannattasio; Marco Foiani; Paolo Plevani (The Scientific World Journal)
DNA polymerase _ (pol _) holds a special position among the growing family of eukaryotic DNA polymerases. In fact, pol _ is associated with DNA primase to form a four subunit complex and, as a consequence, is the only enzyme able to start DNA synthesis de novo. Because of this peculiarity the major role of the DNA polymerase _-primase complex (pol-prim) is in the initiation of DNA replication at chromosomal origins and in the discontinuous synthesis of Okazaki fragments on the lagging strand of the replication fork. However, pol-prim seems to play additional roles in other complex cellular processes, such as the response to DNA damage, telomere maintenance, and the epigenetic control of higher order chromatin assembly.